Training of personnels at the department of biotechnology and bionanotechnology of M.V. Lomonosov Moscow State Academy of Fine Chemical Technology - A. B. Pshenichnikova; V. I. Shvets (Тонкие химические технологии)
Stages of formation of the modern system of training of highly-skilled biotechnological personnel - specialists, bachelors, masters, graduate and doctoral students - at the department of Biotechnology and bionanotechnology of M. V. Lomonosov Moscow State Academy of Fine Chemical Technology are reviewed. The scientific and methodological framework and methodology for biotechnology training were used in the development of the third generation of new State Educational Standards of Higher Professional Education in the direction 240700 Biotechnology (levels of training: bachelor and master).